Perilaku water absorption pada komposit hybrid serat agel tenun dan serat gelas - Hestiawan, H.; Jamasri, J.; Kusmono, K.; Puspawan, A. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2021)
This study aimed to investigate the effect of alkali treatment and stacking sequences on water absorption and flexural strength in woven agel and glass fibers reinforced hybrid composites. The research materials are woven agel fiber, E-200 glass fiber, unsaturated polyester resin Yukalac 157 BQTN, and catalyst of methyl ethyl ketone peroxide (MEKP). The alkali treatment is carried out on the woven agel fibers by soaking the fiber in 5% NaOH solution for 1 hour. Then the fiber is washed with fresh water and dried for 48 hours. Manufacturing techniques used vacuum bagging with suction pressure of 70 cmHg at room temperature. The amount of reinforcing fiber 7 fibers consists of 3 glass fibers and 4 agel woven fibers. The water absorption test uses a 3.5% NaCl solution for 1080 hours at room temperature. Water absorption test specimens based on ASTM D570 standard. The research results showed that alkali treatment with glass fiber arrangement on the specimen surface effectively decreased water absorption and increased the flexural strength of woven agel and glass fibers hybrid composites. This can be seen from the decrease in water content in equilibrium by 8.67%, the diffusion coefficient of 5.74 x 10-12 m2/s, and the flexural strength before and after immersion, which are 135 MPa and 125 MPa respectively.